'What's So Funny?': Videomemes and the Circulation of Contemporary Music in Social Media. Issue 4 (4th July 2022) - Viñuela, Eduardo
Abstract : Prosumers use sound and music as parodic tools to transform the meaning of the original content. These practices give rise to the audio-visual phenomena of videomemes—mash-ups, shreds, literal versions,  … —which have become popular in everyday communication through social media. The selection of a particular piece, genre, or repertoire has social and political implications: it helps establish the position of the person making the selection in online networks and contributes to the negotiation of meaning and canons. Thus, both prosumers and consumers use musical videomenes as cultural artefacts in communication, configuring processes of mutual recognition and interacting in different ways in online communities. In this article, I analyse the circulation of contemporary music videomemes in social media. First, I contextualise the relevance of these amateur productions in the digital era. Then, I discuss the power of parody to reinforce and subvert discourses in this repertoire. Finally, I explore three categories of videomemes—covers, collisions, and shreds—analysing paradigmatic case studies in order to illustrate the most common processes in the creation and circulation of these productions.